STRATEGI PEMBELAJARAN KITAB AKHLAKUL LILBANIN SEBAGAI FILTER AKHLAK SISWA DI MA AN-NUR HA RAMBIGUNDAM RAMBIPUJI JEMBER TAHUN AJARAN 2024/2025 - Hasan, Zainul; Syaehotin, Sayyidah (International Conference on Humanity Education and Society (ICHES), 2025)
Education that is conducted in schools alone is insufficient to filter morality; it also requires collaboration and support from educational institutions outside of schools, such as Islamic boarding schools. Based on this, the purpose of this study is to talk about the methods used to learn the Book of Akhlaq Lil Ba during the academic year 2024–2025 at Madrasah Aliyah An-Nur HA Rambindam, Rambipuji, Jember Regency, using the filter of moral mechanism development. This study employed a qualitative field study approach that uses descriptive interpretation, descriptive methodologies, and observation and documentation studies as well as interviewing approaches to gather data. The study's findings are: Moral development is achieved by the following learning processes: a) learning kitab bandongan; b) classical lectures; c) crossing; d) oral exams; and e) habituation. 2) Adequate learning materials, a welcoming school setting, parental support, and community support in the Rambigundam Village area are all variables that aid in the learning process. 3) The absence of a madrasah guardrail, the existence of students who disobey, the lack of socialization of madrasah laws, and the presence of students who do not complete the allotted tasks are the impeding factors in the book Akhlak lil Banin. 4) To address the challenges in the educational process, the madrasah explains to the parents of the santri why the rules are being implemented at the school, conducts regular checks on the students' records twice a month, and works with the conselor, teaching teacher, and community to discipline any students who behave disrespectfully.